2021
DOI: 10.1364/oe.414387
|View full text |Cite
|
Sign up to set email alerts
|

Efficient InGaAsP MQW-based polarization controller without active-passive integration

Abstract: Carrier-injection-based efficient polarization controller with a strained InGaAsP multiple-quantum-well (MQW) layer is demonstrated on a regrowth-free InP platform. We employ a straight-line device configuration by cascading an asymmetric polarization rotator (PR) to provide a fixed polarization conversion and a polarization-dependent phase shifter (PD-PS) to enable tunable polarization rotation. Based on a novel design concept, both the PR and PD-PS sections are integrated monolithically without active-passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous researches on MQW-based PMCs have mostly focused on fabricating sources of polarization tunable light, and such sources require the PMC to be integrated with a polarization-dependent phase shifter (PD-PS) [6]. In addition, most reports have used relatively complicated butt-joint integration techniques [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches on MQW-based PMCs have mostly focused on fabricating sources of polarization tunable light, and such sources require the PMC to be integrated with a polarization-dependent phase shifter (PD-PS) [6]. In addition, most reports have used relatively complicated butt-joint integration techniques [16].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of these polarization tunable sources is to convert pure TE-or TM-polarized light into an arbitrarily chosen state of polarization, and the PMC is required to have a 50% TE-to-TM polarization conversion efficiency [15]. In addition to the birefringence arising from the waveguide geometry, the birefringence of the MQW also affects the polarization conversion in the PMC [6], with the MQW birefringence having the opposite sign to that arising from the asymmetric waveguide. The effect of MQW birefringence is therefore to increase L π .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sources, detectors, and other components in photonic integrated circuits (PICs). An increasing number of devices including polarization-dependent phase shifters (PD-PSs) [2], [3] and laser diodes (LDs) [4] use multiple-quantum-well (MQW) structures as the active region; it is, therefore, desirable to design PMCs compatible with MQW structures. For a polarization tunable source, the integration of the monolithic PMCs waveguides with LDs requires a good transverse mode-match.…”
mentioning
confidence: 99%
“…For a polarization tunable source, the integration of the monolithic PMCs waveguides with LDs requires a good transverse mode-match. A PMC based on a particular MQW structure design has been reported that can convert TE-or TM-polarized light into an arbitrarily chosen state of polarization (SOP) [2] albeit with only a 50% TE to TM polarization conversion efficiency (PCE) [3]. The crucial issue for MQW PMCs is the inherent birefringence of the MQW, which disturbs the optimal rotation of the SOP on the Poincaré sphere.…”
mentioning
confidence: 99%